Using the Theoretical Domains Framework (TDF) to understand adherence to multiple evidence-based indicators in primary care: a qualitative study. (December 2015) - Lawton, Rebecca; Heyhoe, Jane; Louch, Gemma; Ingleson, Emma; Glidewell, Liz; Willis, Thomas; McEachan, Rosemary; Foy, Robbie
Abstract Background There are recognised gaps between evidence and practice in general practice, a setting posing particular implementation challenges. We earlier screened clinical guideline recommendations to derive a set of 'high-impact' indicators based upon criteria including potential for significant patient benefit, scope for improved practice and amenability to measurement using routinely collected data. Here, we explore health professionals' perceived determinants of adherence to these indicators, examining the degree to which determinants were indicator-specific or potentially generalisable across indicators. Methods We interviewed 60 general practitioners, practice nurses and practice managers in West Yorkshire, the UK, about adherence to four indicators: avoidance of risky prescribing; treatment targets in type 2 diabetes; blood pressure targets in treated hypertension; and anticoagulation in atrial fibrillation. Interview questions drew upon the Theoretical Domains Framework (TDF). Data were analysed using framework analysis. Results Professional role and identity andenvironmental context and resources featured prominently across all indicators whilst the importance of other domains, for example, beliefs about consequences, social influences andknowledge varied across indicators. We identified five meta-themes representing more general organisational and contextual factors common to all indicators. Conclusions The TDF helped elicit a wide range of reported determinants of adherence to 'high-impact' indicators in primary care. It was more difficult to pinpoint which determinants, if targeted by an implementation strategy, would maximise change. The meta-themes broadly underline the need to align the design of interventions targeting general practices with higher level supports and broader contextual considerations. However, our findings suggest that it is feasible to develop interventions to promote the uptake of different evidence-based indicators which share common features whilst also including content-specific adaptations.